Anal Sphincter Injury Associated with Vaginal Twin Delivery - O'Leary, Bobby D.; Bholah, Tariq; Kalisse, Tamara; Hehir, Mark P.; Geary, Michael P. (American Journal of Perinatology, 2019)
Objective Obstetric anal sphincter injury remains the most common cause of fecal incontinence in women, and research in twin pregnancies is sparse. This study aimed to examine risk factors for sphincter injury in twin deliveries over a 10-year period.Study Design This was a retrospective study of twin vaginal deliveries in a tertiary-level hospital over 10 years. We examined the demographics of women who had a vaginal delivery of at least one twin. Logistic regression analysis was used to examine risk factors.Results There were 1,783 (2.1%) twin pregnancies, of which 556 (31%) had a vaginal delivery of at least one twin. Sphincter injury occurred in 1.1% (6/556) women with twins compared with 2.9% (1720/59,944) singleton vaginal deliveries. Women with sphincter injury had more instrumental deliveries (83.3 vs. 27.6%; p = 0.008). On univariate analysis, only instrumental delivery was a significant risk factor (odds ratio: 2.93; p = 0.019).Conclusion Sphincter injury occurs at a lower rate in vaginal twin pregnancies than in singletons. No twin-specific risk factors were identified. Discussion of the risk of sphincter injury should form part of patient counseling with regard to the mode of delivery.
Keywords: obstetric anal sphincter injury; twin delivery; perineal trauma